Malaysian learners and their perceptions towards online English language courses - N. Krishnasamy, Pramela Krish; Wong, Bee Eng (Anadolu University, 2009)
With more emphasis given to the concept of lifelong learning, the number of learners who enroll for distance and online learning programmes in local tertiary institutions has increased. The flexibility of the online learning mode enables learners to prepare themselves to develop confidence and to learn with greater independence. This paper reports the findings of a study on the teaching and learning and technology factors of online English language courses at UNITAR (University Tun Abdul Razak), a virtual university in Malaysia. Both quantitative and qualitative approaches were employed in eliciting data via a questionnaire survey and in-depth interviews. Specifically, the paper reports on learners’ perceptions towards the teaching and learning as well as technology factors during the online English course they were engaged in. The findings with regard to the perceptions of the learners brought more new perspectives which could be incorporated or taken into consideration for an online language learning programme.